Mechanical Characteristics of Glass-Fiber-Reinforced Polyester Composite Materials - Milosan, Ioan; Bedo, Tibor; Gabor, Camelia; Pop, Mihai Alin (MDPI AG, 2025)
Fiber-reinforced composites are gaining more importance across different fields such as aeronautics, automotives, high-performance sporting equipment, etc., where decreasing weight while improving mechanical properties of polymers is fundamental. This article explores the mechanical behavior of fiber-reinforced polyester composite materials, highlighting their advantages and applications in various industrial fields. Usually, composite materials consist of a polyester matrix reinforced with different types of fibers, such as glass, carbon, or Kevlar, which provide superior mechanical characteristics. This study analyzed the tensile strength, bending resistance, and resilience of glass fiber composites, emphasizing the importance of proper fiber selection and manufacturing processes. These materials stand out for their excellent strength-to-weight ratio and are widely used in the fabrication of tanks in various industries. Experimental results demonstrated tensile strength (Rm) around 115 MPa, Shore D hardness values of 88 units, and impact toughness (resilience) of 2.7 J/cm2. Based on the composite materials’ behavior in testing, the article further offers practical recommendations for the effective deployment of these composites in the fabrication of various types of industrial reservoirs.
Keywords: composites; fiber glass; mechanical properties; internal architecture